Segmental Features Contained in BBC Learning English Video: Word in the News - Safira Nur Indriyani; Semi Sukarni; Juita Triana (Scripta : English Department Journal, 2021)
This research is concerned with the segmental features found in BBC Learning English word in the news. The aims of this research are to identify segmental features contained in the BBC Learning English video word in the news and to describe the application of pronunciation in the BBC Leaning English video word in the news in teaching speaking. This research belongs to descriptive qualitative research because the data of this research is collected by classifying the declarative sentences found in the BBC Leaning English video and the researcher as the key instrument. In collecting the data, the researcher opened website BBC Learning English word in the news, chose the video BBC Learning English word in the news, transcript the video, selected the word that contained segmental features, and categorizing the data of segmental features from those video BBC Learning English word in the news. In analyzing the data, the researcher identified the word which contained segmental features, categorizing, counted the number and percentage of the segmental features found, discussed the finding, applied the research finding in teaching speaking, and drew conclusion and suggestion. The result of this research showed that there were 93 segmental features found in video BBC learning English. Based on the types of segmental features, there are three types found, namely 43 vowels (46.24%), 21 diphthong (22.83%), and 28 consonants (30.43%). This result of the analysis can be applied in teaching speaking at vocational high school.